Significant Tumor Inhibition of Trimethyl-152-[L-aspartyl]pheophorbide a in Tumor Photodynamic Therapy≠ - Benić, Anita; Kussayeva, Akmaral; Antol, Ivana; Vazdar, Mario; Brkljača, Zlatko; Chen, Dan-Ye; Yan, Yi-Jia; Gao, Ying-Hua; Chen, Zhi-Long; Margetić, Davor (ChemMedChem, 2025)
A novel pheophorbide derivative, trimethyl-152-[L-aspartyl]pheophorbide a was synthesised and investigated for anti-tumor activity. The prepared photosensitizer had good absorption in the phototherapeutic window and high ROS yields. It exhibited excellent phototoxicity higher than reference compound m-THPC when irradiated by 650 nm light in vitro, and obvious photodynamic anti-tumor effect in vivo. It causes cellular apoptosis or necrosis under laser irradiation and localizes in mitochondria, lysosome, and endoplasmic reticulum. The observed high efficacy was rationalized by efficient introduction into the blood by facile transfer through membranes, which is supported by molecular dynamics simulation studies. This work provides a new candidate photosensitizer for anti-cancer treatment.
Keywords: cancer; nádorové buněčné linie; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; chlorofyl; apoptóza; Drug Screening Assays, Antitumor; Photosensitizing Agents; reaktivní formy kyslíku; fotosenzibilizující látky; screeningové testy protinádorových léčiv; fotochemoterapie; Mice; Cell Proliferation; Cell Line, Tumor; Molecular Dynamics Simulation; Antineoplastic Agents; Reactive Oxygen Species; protinádorové látky; zvířata; vztahy mezi strukturou a aktivitou; Humans; molecular dynamics; Molecular Structure; Photochemotherapy; Chlorophyll; keyword 5; viabilita buněk; Cell Survival; photodynamic therapy; simulace molekulární dynamiky; myši; molekulární struktura; proliferace buněk; Structure-Activity Relationship; pheophorbide; lidé; Apoptosis; Animals